Implementasi Kegiatan Pembelajaran Daring di Masa Pandemi Covid-19 dalam Menstimulasi Kemampuan Calistung Siswa Kelas II SD - Maimunah Sri Hartini; Adisel Adisel; Septi Fitriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the implementation of online learning activities in stimulating the reading, writing and arithmetic (Calistung) ability of class II students of Panca Mukti Village, Central Bengkulu Regency. This research is field research, while the method used is descriptive. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this study are the implementation of online learning activities in stimulating the ability of Calisutug class II children in Panca Mukti Village, Bengkulu Regency, online learning is carried out by utilizing the WhatsApp application, video calls and utilizing LKS learning resources relevant to the material to be delivered, stimulating children's Calisutug abilities Class II of Panca Mukti village, Central Bengkulu Regency, on the ability to read, write and count is still very low, both seen from the attitude during the learning process and the results in learning due to the lack of direct assistance from teachers due to the Covid 19 pandemic conditions. The implementation of online learning activities in stimulating the Calistung ability of grade II children in Panca Mukti village, Central Bengkulu Regency, on the ability to read, write and count is still very low, both in terms of attitudes during the learning process and results in learning due to lack of direct teacher assistance due to pandemic conditions Covid 19. Keywords : Implementation of Online Learning, Stimulating the Ability of Calistung